2018
DOI: 10.3390/s18051574
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Two-Way Satellite Multi-Terrestrial Relay Networks with Hardware Impairments

Abstract: In this paper, we investigate the performance of a two-way hybrid satellite multi-terrestrial cooperative network with hardware impairments (HIs). Particularly, opportunistic relay selection scheme is employed in the considered network, which can substantially enhance the spectral efficiency and spatial diversity gain. By considering both the amplify-and-forward (AF) and decode-and-forward (DF) relay protocols, the closed-form expressions of the outage probability (OP) and throughput for the system are derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Besides, the closed‐form expression for the OP was also derived. In [15], the authors analysed the effect of HIs on the uplink transmission networks in the SatCom with multiple terrestrial relays. Furthermore, the authors proposed a new relay selection scheme for the SatCom.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the closed‐form expression for the OP was also derived. In [15], the authors analysed the effect of HIs on the uplink transmission networks in the SatCom with multiple terrestrial relays. Furthermore, the authors proposed a new relay selection scheme for the SatCom.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that obtaining the closed-form expression of (19) for all values of n ∈ [1, N ] is intractable, not to mention impossible. However, with n = 1, we can obtain the exact expression of the above equation in the following proposition.…”
Section: Lemmamentioning
confidence: 99%
“…in which R ∞,erg nk (γ) is the ergodic rate of x nk in high SNR regime, which can be obtained via yeilding ∆ nk + 1 → ∆ nk and ∆ n +1 → ∆ n from F X nk (γ). After that, substituting the achievable result into (19) to obtain the asymptotic Ergodic rate of x nk . Finally, our work showed that S nk = 0, ∀k, ∀n.…”
Section: E Slope Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Refs. [7,8] study the energy harvesting technique on TWRN under the effect of practical hardware impairments. Finally, physical layer security of AF-TWRN considering imperfect channel state information (CSI) is explored in [9].…”
Section: Introductionmentioning
confidence: 99%